Interactive Geoinformation Three-Dimensional Model of a Landscape Park Using Geoinformatics Tools - Ahmad, M. Ayaz; Tvoroshenko, I.; Baker, Jalal Hasan; Kochura, L.; Lyashenko, V. (IJASEIT, 2020)
The relevance of work is due to the lack of free three-dimensional models of landscape parks and the urgent need to create such models for informing and barrier-free adaptation of users. The current state of cartographic support of landscape parks is low and does not meet users, management, and employees of parks. The object of research is the territory of the multicomplex. The purpose of the research is to develop a three-dimensional model of the regional landscape park for informing and barrier-free adaptation of residents and guests of the city using geoinformatics tools. The methods used in this research are general scientific (system analysis, modeling, higher mathematics) and special methods of mathematical and geoinformation analysis. The work uses the ArcGIS and SketchUp software platforms to create, manage, integrate, analyze, and distribute spatial data. Methods used: geodesy, topography, geoinformatics. The results obtained in the course of the work are of practical importance, are real and tested by the management of the regional landscape park. An interactive three-dimensional geoinformation model implemented in the ArcScene software environment will provide an opportunity further to manage the territory of the regional landscape park. An interactive geoinformation three-dimensional model ensured a 12% increase in the level of informational and barrier-free adaptation of residents and guests on the territory of the multicomplex. The prospects for further research on the creation of a mobile application for park visitors with the ability to search for the nearest bus departure point at their location are determined.
Keywords: data analysis; geoinformatics